The relationship between perceived role and appropriate use of peripherally inserted central catheters: A survey of vascular access nurses in the United States. (June 2017) - Krein, Sarah L.; Kuhn, Latoya; Ratz, David; Winter, Suzanne; Vaughn, Valerie M.; Chopra, Vineet
Abstract: Background: The presence and proliferation of vascular access nursing in hospital settings has been identified as a potential contributor to growing demand, and possible overuse, of peripherally inserted central catheters (PICCs). Objective: We examined vascular access nurses' perceived role related to use of PICCs and the association with appropriateness of PICC use in hospitals. Design: A web-based survey was administered to members of two vascular access professional organizations. Participants: Of 2762 potentially eligible respondents who accessed the link, 1698 (61%) completed the survey. This sample was further restricted to vascular access nurses who worked in a U.S. hospital (n = 1147). Methods: Respondents were categorized based on perceived role: 1) an operator who inserts PICCs; 2) a consultant whose views are not valued by the care team (unvalued consultant); 3) a consultant whose views are valued by the care team (valued consultant). Facility and respondent characteristics, reported practices, leadership support and relationships with other providers were compared across groups using chi-squared tests and analysis of variance. Multivariable logistic regression was used to assess the association between perceived role and reported percentage of PICCs placed for inappropriate reasons. Results: Among the 1147 respondents, 210 (18%) viewed themselves as operators, 683 (59%) as valued consultants, 236 (21%) as unvalued consultants, and 18 (2%) could not be categorized. A significantly higher percentage (93%) of valued consultants reported that vascular access nurses placed the majority of PICCs at their facility, compared to operators (83%) or unvalued consultants (76%) (p < 0.001). After adjustment, compared with operators, valued consultants were significantly more likely to report that <10% of PICCs at their facility were inserted for inappropriate reasons (OR 1.7, p = 0.002); the finding was reversed for unvalued consultants (OR 0.69, p = 0.06). Conclusions: Vascular access nurses and their perceived role as part of the healthcare team are associated with PICC use in hospitals. Strong inter-professional collaboration and respect may help ensure more appropriate use of PICCs.